A review of MXene-derived quantum dots (MQDs): synthesis, characterization, properties and applications - Zhou, Chunhe; Kar, Ban Tan; Han, Wenjuan; Wang, Li; Lu, Ming (Elsevier, 2024)
Cutting MXene to a minimum size and form the derived 2D MXene quantum dots (MQDs), which possess a unique intrinsic layered geometry structure, restricting exciton due to their novel spatial dimension. This gives rise to a broad spectrum of fascinating properties, rendering them for various applications. Herewith, the correlation between composition, structure, and processing control of MQDs is investigated systematically, giving further insight into the intrinsic and extrinsic properties. This review also provides the opportunity to explore new compositions, modify the properties, and tailor these MQDs into the guided architectural design before any prospective applications.